Profanity and the Grotesque in Indra Sinha's Animal's People. Issue 1 (2nd January 2016) - Holoch, Adele
Abstract : This essay examines the use of profanity and the grotesque in Indra Sinha's 2008 novel Animal's People, which fictionalizes the 1984 Union Carbide gas disaster in Bhopal, India. I argue that Sinha's text utilizes the profane to strip away the artifices separating the international readership the novel targets from the subaltern figures upon whom it centres. In doing so, it calls into question attitudes like those employed by Union Carbide when the company's case came to trial, which alleged that US courts and juries would be unable to comprehend the different standards of living accompanying the poverty of Bhopal's citizens. Through readings of Mbembe and Derrida, I discuss the question of what is human, as well as what constitutes human rights, across national and class boundaries. I contend that Animal's process of self-abjection, through frequent sexual references, vulgar language and references to bodily fluids, renders his readers abject as well. Sinha's use of profanity and the grotesque invokes readers' horror and often our laughter, thereby blurring the boundaries between us and involving us and implicating us in complex ways.